Defining novel targets of the plant N-degron pathways - Taylor, Leonard (2023)
The N-degron pathways of targeted protein degradation connect the half-life of a protein to the identity of the amino (N-) terminal residue. The N-degron pathways have been associated with the plant immune response, however, the lack of identified physiological substrates has limited the elucidation of a mechanistic link. Metacaspases (MCs) are cysteine-dependent proteases which have evidenced involvement in programmed cell death and plant defence. Published and unpublished work (VIB, Gent) has revealed the degradomes of MC 1,2,4 and 9. In this thesis, MC degradome data was used to select cleaved Ctterminal proteoforms with amino-terminal destabilising residues of the N-degron pathways. Both in vitro and in vivo assays were used to determine whether the selected proteoforms were degraded through the N-degron pathways. In addition, pathogen elicitors were used to investigate the link between stability of substrates of the N-degron pathways and the plant immune response. The results presented in this thesis demonstrate that D92-REM1.2 is a substrate of the PRT6 N-degron pathway. Furthermore, Y427-ILP1 is shown to be the first identified substrate of the PRT1 N-degron pathways. Additionally, interesting differential effects were observed in substrate stability between the bacterial elicitor flg22 and the fungal elicitor chitin, suggesting to a potential specific role of ATE1 in the plant immune response. Further investigation will be required for the identified substrates; however, this thesis proposes a definitive link between the MC-degradome and the degradation of Ct-p pathways.